Assessing growth and antioxidant properties of greenhouse-grown lettuces (Lactuca sativa L.) under different irrigation and carbon fertilization management - Garmendia, Idoia; Bettoni, Marcelle M.; Goicoechea, Nieves (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
Previous studies demonstrated that moderate water supply restrictions and enhanced CO2 concentration can maintain or improve yield and accumulation of secondary compounds in lettuce under greenhouse conditions. Therefore, the aim of this study was to evaluate the combination of reduced soil moisture content and carbon fertilization in shoot fresh weight (FW) and antioxidant capacity of two Batavia lettuce cultivars (Batabia Rubia Munguia; BRM and Maravilla de Verano; MV). Moderate water restriction treatment was equivalent to 2/3 of the field capacity and elevated CO2 concentration (ECO2) was fixed at ~700 µmol mol-1. While CO2 enrichment exerted a positive effect on shoot FW of MV, especially in combination with water restrictions, the yield of the cultivar BRM was not affected non due to CO2 concentration or irrigation regime. However, antioxidant capacity of BRM plants was increased under ECO2 conditions. These results demonstrate that carbon fertilization and/or moderate water limitations can be strategically used to enhance nutritional value and growth of greenhouse lettuce. Highlights Yield improvement and accumulation of antioxidants were evaluated in lettuce under greenhouse conditions. Enhanced CO2 concentration and water restrictions increased shoot fresh weight of Maravilla de Verano lettuce. Elevated CO2 conditions increased the antioxidant capacity of the cultivar Batavia Rubia Munguia. Moderate water limitations did not significantly diminish the growth of lettuce.